PROVISION OF PUBLIC SERVICES TO THE PEOPLE IN THE MUNICIPALITY PATHUM THANI PROVINCE - Ngamsaad, Benyasiri (Journal of Social Science and Cultural, 2023)
The research having objectives 1) to study the level of people’s demand for municipal services in 2) to study factors affecting people’s demand for municipal services in Pathum Thani Province, this research used quantitative research methodology, data were collected by questionnaires from 400 samples and qualitative research data collection by interviewing 12 key informants. The results of a survey on public demand for municipal services as a whole it was at a high level ( = 3.95, S.D. = 0.865). It was found that public health and environment It is managed in cooperation with the private sector in taking care of Welfare and society Prophylactic injections are available to the general public and children. Disaster prevention and mitigation Health promotion is promoted as prevention. In terms of revenue collection, there is a treasury department that is always on duty and ready to serve the public and private sector in a friendly manner. Services with the private sector / counter service information technology is used And there is always cooperation with private companies to provide services. For this reason, the survey results are at a high average level in all aspects. The result of the stepwise multiple regression analysis revealed that the variables that were significantly related to the needs of the people towards the overall municipal services were Information perception; Knowledge, understanding of the municipality authority; Speed of service; and Equality of service with regression coefficients 0.429, 0.512, 0.642 and 0.896 respectively and predictive coefficient (R2) of 0.792, able to predict the needs of the people towards the overall municipal services at 79.2 percent.